Computer holography becoming practical - Makowski, Michal (Photonics Letters of Poland, 2014)
This editorial contains the overview of the contents of the latest volume of the Photonics Letters of Poland, devoted mainly to holography. The published papers from international research groups show a slow but constant approach of holography towards practical applications in the future. This includes both scientific measurement techniques and future consumer electronics display devices.